Pelatihan GeoGebra Sebagai Media Pembelajaran Inovatif - Erawati Ni Ketut; Ni Kadek Rini Purwati; Ni Wayan Suardiati Putri; I Wayan Gede Wardika (PUAN INDONESIA, 2021)
Learning media is one of the most important learning tools in helping a teacher in delivering material, especially abstract material such as mathematics.Making learning media needs to follow technological advances, to obtain innovative learning media. One of the IT-based mathematics learning media is GeoGebra. Therefore, as a form of lecturer concern in helping teachers develop their abilities and skills in utilizing IT-based media, community service activities are carried out in the form of GeoGebra training as an innovative learning media. Training activities carried out at SMP N 4 Sukawati was in the form of introduction and training as well as GeoGebra assistance. Based on the training activities that have been carried out, it can be seen that the teacher shows an enthusiastic attitude and is willing to learn using GeoGebra software. Teachers quickly receive training materials and can operate or design the media, so the training provides positive feedback. Therefore, this training activity is expected to become an ongoing activity to improve the ability of teachers, especially in designing an IT-based learning media. As well as spreading the willingness of teachers to train skills in developing IT-based media to other schools.